The Federal Democratic Republic of Ethiopia : 2005 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for The Federal Democratic Republic of Ethiopia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The Federal Democratic Republic of Ethiopia's 2005 Article IV Consultation reports that domestic credit growth has accelerated, driven by strong demand from the government, public enterprises, and the private sector. High import content, particularly from public infrastructure investments, together with higher oil imports, has translated into widening trade and current account deficits, and emerging pressures on international reserves. Inflation pressures are rising, driven by both demand pressures and higher import costs. The real effective exchange rate has appreciated moderately.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet